Development Of Ball Control Exercises Using Feet In Teqball Games For Pjkr Students - Kahfi, Muhammad Ashhabul; Sardiman, Sardiman; Agusman, Muhammad; Saparia, Andi; Syahban, Arham (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to develop variations of ball control exercises using the feet in teqball games for PJKR students. The research method used is Research and Development (R&D) with Borg & Gall stages that include needs analysis, product development, expert validation, and small group and large group trials. Validation was carried out by a learning expert and two teqball experts, with results of 65%, 77%, and 71%, respectively, indicating that the product is considered feasible with revisions. The small group trial involving 15 students resulted in a feasibility percentage of 78.86%, so the training model was declared effective and can be used. However, the large group trial with 20 students showed a percentage of 58.46%, indicating that some training variations need to be improved to be suitable for groups with a larger number of participants and more diverse abilities. Overall, the results of the study indicate that the training model has strong potential to improve ball control skills, but requires refinement in several forms of training to be optimally applied in teqball learning.